2010
DOI: 10.1152/ajprenal.00502.2009
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in dietary K intake stimulates the generation of superoxide anions in the kidney and inhibits K secretory channels in the CCD

Abstract: We previously demonstrated that K depletion inhibited ROMK-like small-conductance K channels (SK) in the cortical collecting duct (CCD) and that the effect was mediated by superoxide anions that stimulated Src family protein tyrosine kinase (PTK) and mitogen-activated protein kinase (MAPK) (51). However, because animals on a K-deficient diet had a severe hypokalemia, superoxide-dependent signaling may not regulate ROMK channels under physiological conditions with a normal plasma K concentration. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
0
12
0
4
Order By: Relevance
“…Immunohistochemical analysis shows that ROMK channels are specifically localized to the apical membrane of the epithelial cells (291, 396, 655, 658). Electrophysiological studies confirmed apical localization of ROMK channels (164, 167, 323, 325, 620, 627). K + channel activity was absent in the apical membranes of either TAL or CCD of ROMK −/− mice (342).…”
Section: Introductionmentioning
confidence: 64%
“…Immunohistochemical analysis shows that ROMK channels are specifically localized to the apical membrane of the epithelial cells (291, 396, 655, 658). Electrophysiological studies confirmed apical localization of ROMK channels (164, 167, 323, 325, 620, 627). K + channel activity was absent in the apical membranes of either TAL or CCD of ROMK −/− mice (342).…”
Section: Introductionmentioning
confidence: 64%
“…Although p38 and ERK1/2 pathways seem to be part of AT1Rdependent inhibition of ROMK channels during LK diets (Babilonia et al, 2006;Jin et al, 2009), tyrosine phosphorylation of ROMK by c-Src is the most important signaling pathway directly responsible for ROMK inhibition during potassium restriction. While collecting ducts from rats fed LK diets do not show relevant ROMK-like small conductance K + currents, these same collecting ducts presented a significant increase in the number of ROMK-like channels in patch-clamp recordings when the collecting duct cells were acutely treated with c-Src inhibitor herbimicyn A for 30 min, an effect that does not occur in rats receiving HK diets (Wang et al, 2000(Wang et al, , 2010. Also, in the collecting ducts from animals receiving LK diets, the acute treatment with c-Src inhibitor herbymicin A majorly abolishes the Ang II inhibitory effect over ROMK activity (Wei et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…A recent study by this group further demonstrated that all of these changes occurred with normal plasma [K + ] in rats and mice maintained on a low (0.1%) K + diet (49). Our previous study also showed that modest K + deprivation increases PTK expression and ROMK phosphorylation in the absence of a fall in plasma K + or aldosterone levels (50).…”
Section: Mechanisms Of the Gut-factor Effectsmentioning
confidence: 93%
“…Regarding this alternative, a strong candidate for such a factor is reactive oxygen species (ROS) including superoxide anions. As discussed above, Wang and colleagues have suggested that renal K + adaptation is mediated by changes in superoxide anion production in the kidneys, which occurred even with normal plasma [K + ] (48, 49). On the other hand, recent studies have suggested that ROS is involved in detrimental effects of low K + diet and protective effects of high K + diet on the cardiovascular system (63, 64).…”
Section: Beneficial Effects Of Dietary Potassiummentioning
confidence: 99%
See 1 more Smart Citation